IMPLEMENTATION OF TEACHER TEACHING SKILLS IN CLASSROOM LEARNING - Yosep Heristyo Endro Baruno; Yosua Padama (Indonesian Journal of Education (INJOE), 2024)
Basic teaching skills are an important aspect that teachers must have in order to carry out their role in managing the learning process. Competent teachers will be better able to create an effective learning environment and be able to manage their classes, so that student learning outcomes can be achieved optimally. A teacher in learning must have basic teaching skills, namely in the initial/opening activities, core activities, and closing activities. These three activities are the main activities and must be carried out in learning. In connection with research regarding teachers' teaching skills, the material for measuring the basic skills of implementing learning was observed by researchers through observation sheets. Increasing teacher efforts can be done by broadening horizons, developing the learning environment, utilizing various learning resources, and providing rewards as teacher appreciation for students' enthusiasm for learning. The teacher's skill in carrying out learning from start to finish can make students happier participating in learning activities.